HUBUNGAN BBLR DENGAN KEJADIAN HIPOTERMIA PADA BAYI - Roudatul Hikmah (Oksitosin : Jurnal Ilmiah Kebidanan, 2016)
The risk of hypothermia incidence increasing with the number of babies born with low birth weight (LBW). Premature infants and term infants are born with low birth weight, especially below 2000 grams, threatened with death due to hypothermia because babies with low birth weight (LBW) are very susceptible to problems on increasing heat loss. This study aimed to determine the relationship with the incidence of LBW hypothermia. This research used analytic survey documentation. The sampling method used total sampling with 105 respondents LBW. Techniques of data collection used checklist instruments were written from medical record. Further processing and analysis used product moment test by comparing the significant level (p-value) with the error Researched result showed that the obtained value of 0.002 sgn so H0 is rejected, which means that there was a significant correlation (0.002 <0.05) between the incidence of LBW with hypothermia. Keywords: Low Birth Weight (LBW), Hypothermia ABSTRAK Bayi premature maupun bayi cukup bulan yang lahir dengan berat badan rendah terutama dibawah 2000 gram, terancam kematian akibat hipotermi karena bayi dengan berat badan lahir rendah (BBLR) sangat rentan mengalami permasalahan pada peningkatan kehilangan panas. Penelitian ini bertujuan untuk mengetahui hubungan BBLR dengan kejadian. Jenis penelitian ini menggunakan survey analitik dengan pendekatan Dokumentasi. Metode sampling yang digunakan yaitu total sampling dengan jumlah responden 105 BBLR. Teknik pengambilan data dengan instrumen cheklist yang dicatat dari medical record. Selanjutnya pengolahan dan analisa data menggunakan uji product moment. Hasil penelitian menunjukkan bahwa diperoleh nilai sIgn sebesar 0,002 sehingga H0 ditolak yang artinya ada hubungan yang signifikan yaitu (0,002<0,05) antara BBLR dengan kejadian hipotermia. Kata kunci : Berat Badan Lahir Rendah (BBLR), Hipotermia.